Determination of monthly changes in mineral content of spiny Atraphaxis (Atraphaxis spinosa L.) as an alternative fodder crop - Keskin, Bilal (Progress in Nutrition, 2018)
This study was conducted in 2015 with the aim of determining monthly changes in mineral content of Spiny Atraphaxis (Atraphaxis spinosa L.) as to growth phases. Wild plants grown spontaneously on the wind erosion site in Aralık district of Iğdır province were the subject of the study. Plant samples were collected and changes in N (Nitrogen), P (Phosphorus), K (Potassium), Ca (Calcium), Mg (Magnesium), Na (Sodium), Cu (Copper), Fe (Iron), Zn (Zinc) and Mn (Manganese) contents were determined according to months. Highest values for N, P, K, Ca, Mg, Na, Cu, Fe, Zn and Mn contents of Spiny Atraphaxis during the 7-month growth period within which this study was conducted were measured as, 1.27%,  0.98%,  1.46%,  1.17%,  0.46%,  0.19%, 2.66 ppm, 344.76 ppm, 42.46 ppm and 64.90 ppm, respectively.